EU OG ERHVERSLIVET: HVAD KAN UDVIKLINGEN AF EU’S LANDBRUGSPOLITIK FORTÆLLE OS? - Nedergaard, P. (Tidsskrift for Landøkonomi, 2008)
EU OG ERHVERSLIVET: HVAD KAN UDVIKLINGEN AF EU’S LANDBRUGSPOLITIK FORTÆLLE OS?